Preliminary findings of quorum signal molecules in clinically stable lung allograft recipients. Issue 5 (1st May 2003) - Ward, C; Cámara, M; Forrest, I; Rutherford, R; Pritchard, G; Daykin, M; Hardman, A; de Soyza, A; Fisher, A J; Williams, P; Corris, P A
Abstract : Background: Infection with bacteria such as Pseudomonas is common in lung allograft recipients, particularly during chronic rejection. Analysis of sputum samples from patients with cystic fibrosis infected with Pseudomonas aeruginosa or Burkholderia cepacia has indicated the presence of bacterial N -acylhomoserine lactones (AHLs) quorum sensing signalling molecules. AHLs not only control the expression of bacterial virulence genes but are also involved in stimulating the maturation of antibiotic resistant biofilms and host chemokine release. It was hypothesised that AHLs may be detected even in clinically stable lung transplant recipients free of clinical infection or rejection. Methods: Three 60 ml samples of bronchoalveolar lavage (BAL) fluid were taken from nine stable lung transplant recipients 3–12 months after transplantation. Detection of AHLs was carried out on dichloromethane extracted supernatants using the bioluminescence based AHL reporter plasmid pSB1075. This responds to the presence of AHLs with long acyl chains (C10–C14), generating light. Synthetic AHLs were included as positive controls. Results: Five of the nine BAL fluid supernatants exhibited AHL activity, suggesting the presence of AHLs with long N-acyl chains. There was no correlation between the levels of AHLs detected or their absence and BAL fluid microbiology or diagnosis before transplantation. Conclusions: This is the first evidence for the presence of AHL quorum sensing signals in human lung allograft recipients, even in subjects with no rejection or apparent infection. Further longitudinal follow up of these preliminary findings is required to elucidate potential links with infection, rejection, and allograft deterioration.